A portfolio approach to managing ecological risks of global change. Issue 2 (24th February 2017) - Aplet, Gregory H.; McKinley, Peter S.
Abstract: The stressors of global environmental change make it impossible over the long term for natural systems to maintain their historical composition. Conservation's new objective must be to maintain the building blocks of future systems (e.g., species, genes, soil types, and landforms) as they continuously rearrange. Because of the certainty of change, some biologists and managers question continued use of retrospective conservation strategies (e.g., reserves and restoration) informed by the historical range of variability. Prospective strategies that manage toward anticipated conditions have joined the conservation toolbox alongside retrospective conservation. We argue that high uncertainty around the rates and trajectories of climate and ecological change dictate the need to spread ecological risk using prospective and retrospective strategies across conservation networks in a systematic and adaptively managed approach. We term this a portfolio approach drawing comparisons to financial portfolio risk management as a means to maximize conservation benefit and learning. As with a financial portfolio, the portfolio approach requires that management allocations receive minimum temporal commitments to realize longer‐term benefits. Our approach requires segregation of the strategies into three landscape zones to avoid counterproductive interactions. The zones will be managed to (1) observe change, (2) resist change, and (3) facilitate change. We offer guidelines for zone allocation based on ecological integrity. All zones should follow principles of conservation design traditionally applied to reserves. Comparable to financial portfolios, zone performance is monitored to facilitate learning and potential reallocation for long‐term net minimization of risk to the building blocks of future ecosystems.